PELAKSANAAN KOMUNIKASI INTERNAL KETUA YAYASAN ARRISALAH ALKHAIRIYAH DALAM MENINGKATKAN KINERJA PEGAWAI DI DESA BANGUN SARI KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG - Dori Candra (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2017)
Abstrak: This research is aimed to : 1) analyze the communication between the director of foundationand the head of branch in inncreasing the staff capability of ArRisalah AlKhairiyah Foundation, 2) analyzethe communication between the director of foundation and the staff to improve their capabilities, 3) analyzethe communication between the director and the conselor of foundation in inncreasing the staffcapability of ArRisalah AlKhairiyah Foundation. The qualitative methodology of research was used bythe writer since it due to search the social phenomena and the issues of human beings. The source of datataken from interview, observation and other documentation due to this research.